2016
DOI: 10.1016/j.jallcom.2016.04.309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of copper composition and reaction temperature on the properties of CZTSe thin films

Abstract: a b s t r a c tIn this study Cu 2 ZnSnSe 4 (CZTSe) compound layers were grown using a two-stage technique that involved deposition of metallic precursors (Cu, Zn, and Sn) and Se in the first stage, followed by reaction of all the species at temperatures between 525 C and 600 C, during the second stage of the process. Two sets of samples, one with Cu-poor, Zn-rich and the other with Cu-rich, Zn-rich compositions, were prepared and their structural, optical and electrical properties were measured. XRD analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the first part, deposition methods can be categorized as vacuum and non-vacuum techniques. Vacuum methods are for example pulsed laser deposition [5], thermal evaporation [6,7], e-beam evaporation [8], and magnetron sputtering [9][10][11][12]. The most commonly used non-vacuum methods are electrodeposition [13][14][15], spray pyrolysis [16,17], sol-gel deposition [18], doctor-blading or spincoating of nanoparticles [19,20], or spin-coating or spray-deposition of molecular precursors [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the first part, deposition methods can be categorized as vacuum and non-vacuum techniques. Vacuum methods are for example pulsed laser deposition [5], thermal evaporation [6,7], e-beam evaporation [8], and magnetron sputtering [9][10][11][12]. The most commonly used non-vacuum methods are electrodeposition [13][14][15], spray pyrolysis [16,17], sol-gel deposition [18], doctor-blading or spincoating of nanoparticles [19,20], or spin-coating or spray-deposition of molecular precursors [21].…”
Section: Introductionmentioning
confidence: 99%
“…After the Se evaporation step, the (Cu-Zn-Sn)/Se precursor layers were reacted for 15 min in a tube furnace in a static 5%H 2 + 95%Ar atmosphere at 550°C. For simulating a rapid thermal process, the tube furnace with the process gas was first heated to the reaction temperature and the samples were then rapidly pushed into the hot zone [11]. The estimated ramping rate of the temperature in these experiments was about 5°C/s.…”
Section: Methodsmentioning
confidence: 99%
“…Since the CZTSe thin films were grown on conductive and non-transparent substrates, optical transmission and the electrical measurement in the plane of the films could only be performed after they were transferred from their substrates onto glass slides by transparent epoxy peeling approach as previously utilized by Basol [19]. The detailed experimental procedures used for mechanical transfer of the reacted films onto glass were described in our recent publication [11]. The crystalline structure and the structural quality of the films were determined by XRD measurements using a Rigaku SmartLab diffractometer with a CuKα radiation source (λ = 1.5405 Å) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reported studies have focused on the optimizing fabrication parameters of the CZTS absorber layer since solar cell efficiency is strongly-dependent on the quality of the absorber layer. These studies include optimization of the sulfurization temperature [13] , sulfurization time [14], variation order of the metallic stack [15], composition of film [16,17], and the pressure of the sulfurization [18,19] etc. The prior works have suggested that although high reaction temperatures (> 500 °C) may enhance the grain morphology, it also gives rise to loss of Sn and Zn thanks to the high vapor pressure of SnS and Zn [20].…”
Section: Introductionmentioning
confidence: 99%